The analysis of financial performance using financial ratios approach and common size approach: a case of GE Engine Services (M) Sdn Bhd / Norfarahin Md Ghazali - Md Ghazali, Norfarahin (Faculty of Business and Management, 2012)
This study is concern to the GE Engine Services (M) Sdn Bhd performance as the significant indicator of having a good financial performance. In order to obtain a good financial performance, an appropriate analysis or evaluation need to be conducted. Rationally, the purpose of preparing and analysis or evaluation is to show it establishing of a company depend to its financial performance and have an ability to manage the utilization of its sources. With the stability of its financial performance, there is no impossible to a company to have continuous operation. An analysis or the evaluation can be conducted with assist from financial statement and a balance sheet. The financial tools will be used to measure the company’s performance. The analytical tools such as financial ratio will be measured as represented in the financial statement dated 2007 to 2011. Each of financial ratios bringing the different kind of description to is as the evaluation or the analysis after being done. There are several different of financial ratios, which are consists of liquidity ratio, assets utilization ratios, leverage ratios and profitability ratios. Based on the research, researcher found that GE Engine Services (M) Sdn Bhd facing the net profit towards the profits and it was high credit (risk) regarding the debt ratio. Indeed, the good management from its assets will affect the financial performance. For recommendation, reduce expenses and arise the profits in their sales or revenue. Thus, the actual margin of the analysis describes the details of the financial ratios.